Paradoksi branja in znanja v Sloveniji - Kovač, Miha (Knjižnica, 2009)
The paper introduces the concept of book usage and puts Slovenian book usage into the context of the European Union. It stresses the limits of European book statistics, due to them the measurements of book usage in various European societis is almost impossible. In this context, we will show that due to available data, Slovenia paradoxically belongs to the countries with high book usage and average reading habits. In the second part of the paper, we will look at the correlations between reading habits and efficiency of education systems. On this basis, we will ask some new questions and develop a set of hypotheses that need to be verified by the further research.
Keywords: založništvo; knjigotrštvo; knjige; e-knjige; branje; bralne navade; raziskave; Slovenia; Slovenija